Sistem Pakar untuk Menentukan Penyakit dengan Gejala Kaki Bengkak Menggunakan Metode Forward Chaining - Yurian Prabowo (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Abstract— Leg swelling is a symptom of a disease that can cause death if left untreated. Treating the symptoms of swollen legs needed an expert in the field of health. An expert system is a system that adopts human knowledge to solve a specific problem usually needed an expert. The expert system will be used to assist users in diagnosing diseases that lead to leg swelling. An expert system will be developed with a forward chaining method and the method of representation of production rules. System that has been built has been tested with 50 cases of medical records, which the system can diagnose 76% of the disease if the data is complete and detailed, but is only able to diagnose 22% to 32% if the data is incomplete.